Formulation of Business Development Strategy For Diagnostic Laboratory Instrument at PT XYZ - Hafizh Nalviando; Dikky Indrawan; Siti Jahroh (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The healthcare industry, particularly the diagnostic sector, is experiencing fast growth. PT XYZ along with similar companies, is competing for market share, but PT XYZ only captures a very small share. Furthermore, annual performance in three years has stagnated with poor achievement. Therefore, a business development strategy is needed to increase market share and company performance. Purpose: This research aims to formulate a laboratory instrument business development strategy by identifying external and internal factors and formulating alternative strategies to develop PT XYZ's laboratory instrument business. Design/methodology/approach: The research employs a combination of PESTEL and Porter’s Five Forces for external environmental analysis, while internal factors are analyzed using the VRIO framework and Value Chain Analysis. Data collection involved in-depth interviews and structured questionnaires, synthesizing insights from both internal and external experts to ensure a comprehensive understanding of the current strategic position.Findings/Result: PT XYZ is positioned in the “Grow and Build” quadrant based on the IE Matrix, with an EFE score of 3.27 and an IFE score of 2.23. This indicates that PT XYZ is able to respond effectively to key external factors and adequately leverage its internal strengths. Therefore, future strategy formulation should be directed toward business growth and development. Based on the SWOT analysis, seven strategic initiatives for the development of the diagnostic laboratory equipment business are recommended for PT XYZ.Conclusion: PT XYZ is very strong in responding to external factors. Although PT XYZ is quite sufficient in maximizing internal factors. The formulation of a strategy for PT XYZ is to grow and build with seven alternative business development strategies.Originality/value (State of the art): This study adopts a distinctive and application-oriented approach to business strategy formulation within the in vitro diagnostic sector, thereby providing strategic recommendations that support companies in enhancing their competitiveness in the market. Keywords: laboratory diagnostic instrument, strategy formulation, business development, healthcare industry, business strategy